Revitalizing the blood culture volume! - Zainulabid, Ummu Afeera; Danapaul, Nabil Anaz Anzani; Chee, Lan Lau; Kori, Najma; Abd Rahim, Yusuf Zawir; Periyasamy, Petrick (2023)
Blood cultures are undoubtedly the most critical investigation for bloodstream infections. However, insufficient blood culture volumes frequently impair diagnostic yield. Thus, we investigated the volume of blood culture bottles being filled at our institution. Then we looked at whether an educational intervention could increase the volume of blood culture bottles.